2016
DOI: 10.1111/cmi.12560
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium nucleatuminfection of gingival epithelial cells leads to NLRP3 inflammasome-dependent secretion of IL-1β and the danger signals ASC and HMGB1

Abstract: Summary Fusobacterium nucleatum is an invasive anaerobic bacterium that is associated with periodontal disease. Previous studies have focused on virulence factors produced by F. nucleatum, but early recognition of the pathogen by the immune system remains poorly understood. Although an inflammasome in gingival epithelial cells (GECs) can be stimulated by danger-associated molecular patterns (DAMPs) (also known as danger signals) such as ATP, inflammasome activation by this periodontal pathogen has yet to be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 54 publications
5
93
3
2
Order By: Relevance
“…NLRP3 inflammasome activation activates caspase 1 and induces secretion of mature IL‐1β. Also, an F. nucleatum infection can induce other damage‐associated molecular patterns that mediate inflammasomes, including high‐mobility group box 1 protein (HMGB1) and apoptosis‐associated speck‐like protein (ASP), with a time course similar to that of caspase 1 activation . Studies have found that P. gingivalis is detected frequently in esophageal cancer and dysplasia tissues but rarely in noncancerous and normal tissues .…”
Section: Discussionmentioning
confidence: 99%
“…NLRP3 inflammasome activation activates caspase 1 and induces secretion of mature IL‐1β. Also, an F. nucleatum infection can induce other damage‐associated molecular patterns that mediate inflammasomes, including high‐mobility group box 1 protein (HMGB1) and apoptosis‐associated speck‐like protein (ASP), with a time course similar to that of caspase 1 activation . Studies have found that P. gingivalis is detected frequently in esophageal cancer and dysplasia tissues but rarely in noncancerous and normal tissues .…”
Section: Discussionmentioning
confidence: 99%
“…Although incompletely understood, GI inflammation‐mediated progression to cancer development might involve bacterial toxin production, release of alarmins, gut biofilm modification, dysregulation of gut barrier function, suppression of anti‐inflammatory mediators and transition through an element of high grade dysplasia to cell damage and aneuploidy 13, 19, 35, 40, 60, 61, 62…”
Section: Discussionmentioning
confidence: 99%
“…The limited expression of these pattern recognition receptors might contribute to their low sensitivity to microbial ligands. However, live bacteria in dental plaque may play more important roles in epithelial cell death than bacterial remnants in dental calculus …”
Section: Discussionmentioning
confidence: 99%
“…These epithelia act as the first line of defense against invading bacteria and other external stimuli, protecting periodontal tissue as a physical barrier . While epithelial cells are not an authentic inflammatory cell type and cannot be the dominant source of IL‐1β, they express NLRP3 inflammasome components . Upon activation of NLRP3 inflammasome, caspase‐1 cleaves a 53 kDa substrate called gasdermin D, and the N‐terminal fragment of gasdermin D assembles into pores in the cell membrane, which causes cell death, pyroptosis .…”
Section: Introductionmentioning
confidence: 99%